Instrument development and preliminary validation of a scale assessing pre-nursing students’ perceived instructor care in anatomy and physiology - Khalaf, Nicola; Zhang, Jingshun; Craddock, Jason; Weiss, Valerie; Sillevis, Rob (Frontiers in Education, 2026)
BackgroundWhile numerous studies have shown a correlation between student-instructor rapport and student academic performance, few studies have investigated the relationship between students’ perception of instructor care and academic performance, particularly in gateway STEM courses. Anatomy and Physiology, a gateway course to nursing programs, is generally associated with high rates of unsuccessful outcomes.MethodA psychometric instrument was developed to identify the attributes that pre-nursing students perceive as indicators of instructor care. The instrument also measures the extent to which students attribute instructors’ care to their academic performance in Anatomy and Physiology. A preliminary validation of the instrument was completed to assess its reliability and validity.ResultsThis paper describes a pilot study to assess the reliability and preliminary validation of the instrument.ConclusionThis tool contributes to existing scholarly work on student–instructor relationships and supports institutional decisions aimed at improving student academic performance. However, full empirical and structural validation of the instrument is reserved for future large-sample studies to further establish its factor structure, stability, and generalizability.